Can intraoral scanning an alternative to clinical visual assessment in dental plaque scoring - MEŞELİ, SİMGE; KORKUT, BORA; TAĞTEKİN, DİLEK (My University, 2023)
Aim: The aim of this study was to compare the clinical visual examination and intraoral scanning methods for the assessment of dental plaque scores. And also to assess the effect of plaque staining on the scores. Materials and Methods: Twenty-eight volunteers between the age of 18-45 were included in the study. The volunteers were divided into two groups according to DMFT (D: Decayed, M: Missing, F: Filling T: Teeth) scores [low DMFT group (scores under 4), high DMFT group (scores over 10)].The level of dental plaque on buccal and lingual surfaces of all teeth was scored by using clinical visual examination with and without staining and also by intraoral scanning (iTero Element Flex, Align Technologies, San Jose, California) with staining. Dental plaque scoring was performed with the Turesky Modified Quigley Hein Plaque Index through the clinical visual examination and the scanned intraoral images. The comparisons between the clinical visual examination and intraoral scanning scores were analyzed by Mann Whitney U and Friedman Tests using the IBM SPSS Statistics V23. The deem significance was set at p<0.05. Results: In low DMFT group, In the low DMFT group, unstained clinical visual examination scores were significantly lower than stained visual examination scores and intraoral scanning scores (p<0.001). However, there was no significant difference among all the three imaging methods regarding the high DMFT group, in terms of the plaque scores (p=0.441). Conclusion: The staining of dental plaque might have a positive effect for the determination of the plaque clinically, for the patients with low DMFT scores. The intraoral scanningmay be used as an alternative method to the conventional clinical plaque indices which are used through the clinical visual examination, and also to educate and motivate thepatients about the plaque control and the oral care.
Keywords: Dental Plaque; Plaque Indices; Intraoral Scanner; Dental Plaque Staining; Dental Plaque Imaging